2009
DOI: 10.1137/080717602
|View full text |Cite
|
Sign up to set email alerts
|

A Finite Element Method for Elliptic Equations on Surfaces

Abstract: Abstract. In this paper a new finite element approach for the discretization of elliptic partial differential equations on surfaces is treated. The main idea is to use finite element spaces that are induced by triangulations of an "outer" domain to discretize the partial differential equation on the surface. The method is particularly suitable for problems in which there is a coupling with a flow problem in an outer domain that contains the surface. We give an analysis that shows that the method has optimal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
214
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 175 publications
(215 citation statements)
references
References 11 publications
(14 reference statements)
0
214
0
1
Order By: Relevance
“…Descripton of the method. In this section we describe the finite element method from [7] for the three-dimensional case. The modifications needed for the two-dimensional case are obvious.…”
Section: Surface Finite Element Methodmentioning
confidence: 99%
See 4 more Smart Citations
“…Descripton of the method. In this section we describe the finite element method from [7] for the three-dimensional case. The modifications needed for the two-dimensional case are obvious.…”
Section: Surface Finite Element Methodmentioning
confidence: 99%
“…In [7] it is shown that this new method has optimal order of convergence in H 1 and L 2 norms. The analysis requires shape regularity of the outer triangulation, but does not require any type of shape regularity for discrete surface elements.…”
mentioning
confidence: 99%
See 3 more Smart Citations